The scorpion's tail : a Nora Kelly novel - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J Nora Kelly, 2021)
A sequel to "Old Bones" finds FBI agent Corrie Swanson and Santa Fe archaeologist Nora Kelly investigating the mummified corpse of a long-dead victim who died in agony while holding a mysterious sixteenth-century gold cross.